A general multi-objective topology optimization methodology developed for customized design of pelvic prostheses. (July 2019) - Iqbal, Taimoor; Wang, Ling; Li, Dichen; Dong, Enchun; Fan, Hongbin; Fu, Jun; Hu, Cai
Highlights: Multi-objective topology optimization method for design of pelvic prostheses. Multi daily activities were considered for biomechanics study of human pelvis. Optimized 3D printed pelvic implant for resection type 2+3 was applied clinically. Abstract: In this study, a multi-objective topology optimization method has been formulated and carried out for various resection types, with minimization of a weighted sum of the compliance (maximized stiffness) under six routine activities of daily life as the objective function and volume reduction as a constraint. Unique prosthetic geometries with low weight and remarkable strength closely matching the pelvic bone shape were obtained. The strength of the optimized implants was investigated through finite element analysis and it has been found that the initial geometries of the optimized implants could withstand the static loading conditions of various routine activities having less stress concentration areas. A 3D printed patient-specific topology optimized hemi-pelvic prosthesis has been designed based on the proposed method and implanted successfully in a patient with pelvic sarcoma. Therefore, pelvic prostheses can be designed and then manufactured via additive manufacturing technologies with the minimum material in less time and having robust mechanical fixation responses. Conclusively, the topology optimization method used for the design of pelvic prostheses improves the biomechanical performance of the implants with reduced weight and higher stiffness than the traditional implants. Including the topology optimization procedure in the phase of designing patient-specific pelvic implants is therefore, highly recommended.